2010
DOI: 10.1149/1.3483752
|View full text |Cite
|
Sign up to set email alerts
|

Tribological, Thermal, and Wear Characteristics of Poly(phenylene sulfide) and Polyetheretherketone Retaining Rings in Interlayer Dielectric CMP

Abstract: Retaining rings made of poly͑phenylene sulfide͒ ͑PPS͒ and polyetheretherketone ͑PEEK͒ with two different slot designs were subjected to a 4 h wear test. During the chemical mechanical planarization ͑CMP͒ process, the PPS retaining ring induced a higher coefficient of friction ͑COF͒ by ϳ0.1 than the PEEK retaining rings. In addition, the PPS retaining ring exhibited a higher wear rate than the PEEK retaining rings by ϳ28%. Although the retaining ring slot design did not significantly affect the COF and wear rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…The solution in the flask was maintained at a temperature of 40 • C using a hot plate, to better mimic the actual temperature during CMP, 12 and was stirred using a magnetic stirrer to reduce mass transfer limitations for material removal from the surface into the solution. Before the dissolution experiment, the GaAs coupon was dipped in a 2 M aq.…”
Section: Methodsmentioning
confidence: 99%
“…The solution in the flask was maintained at a temperature of 40 • C using a hot plate, to better mimic the actual temperature during CMP, 12 and was stirred using a magnetic stirrer to reduce mass transfer limitations for material removal from the surface into the solution. Before the dissolution experiment, the GaAs coupon was dipped in a 2 M aq.…”
Section: Methodsmentioning
confidence: 99%
“…The solution was stirred using a magnetic stirrer at 500 rpm rotational speed to minimize mass transfer effects and the temperature was maintained at 40 • C to mimic more closely the anticipated temperature during CMP. 16,17 The coupon was removed, washed repeatedly with deionized (DI) water, dried in a N 2 stream, and reweighed. The weight loss was used to calculate the dissolution rate and the reported rates were obtained by averaging over three experiments, each spanning at least 1 min.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…10 With lower frictional forces generated at the retaining ring-slurry abrasives-pad interface, the PEEK retaining ring induces a lower pad wear rate and provides benefits with a longer pad life and lower cost of ownership for CMP processes.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous study, similar frictional forces were reported for the PEEK-1 and PEEK-2 retaining rings. 10 As the PEEK-1 and PEEK-2 retaining rings generate similar frictional forces among the retaining ring surface, slurry abrasives, and pad surface, they result in similar pad wear rates. Figure 3 also shows that for both retaining rings, the wear rate for the D100 pad is significantly lower than that for the IC1000 pad.…”
Section: Methodsmentioning
confidence: 99%